Bereavement care and the interaction with relatives in the context of euthanasia: A qualitative study with healthcare providers. (April 2023) - Boven, Charlotte; Van Humbeeck, Liesbeth; Van den Block, Lieve; Piers, Ruth; Van Den Noortgate, Nele; Dillen, Let
Abstract: Background: A recent review shows an interdependence between healthcare providers and relatives in the context of euthanasia. Belgian guidelines do focus on the role of certain healthcare providers (physicians, nurses, and psychologists), yet they hardly specify bereavement care services before, during and after the euthanasia. Purpose: A conceptual model showing underlying mechanisms of healthcare providers' experiences regarding the interaction with and the provision of bereavement care to relatives of cancer patients throughout a euthanasia process. Methods: 47 semi-structured interviews with Flemish physicians, nurses and psychologists working in hospitals and/or homecare, conducted from September 2020 to April 2022. Transcripts were analyzed using the Constructivist Grounded Theory Approach. Results: Participants experienced the interaction with relatives as very diverse, which can be visualized as a continuum ranging from negative to positive, depending on each unique case. The achieved degree of serenity was the main contributor in determining their position on the aforementioned continuum. To create this serene atmosphere, healthcare providers undertook actions underpinned by two attitudes (wariness and meticulousness), which are guided by different considerations. These considerations can be categorized into three groups: 1) ideas about a good death and its importance, 2) having the situation well under control and 3) self-reassurance. Conclusions: If relatives were not at peace, most participants said that they deny a request or formulate additional requirements. Moreover, they wanted to ensure relatives can cope with the loss, which was often experienced as intense and time-consuming. Our insights shape needs-based care from healthcare providers' perspective in the context of euthanasia. Future research should explore the relatives' perspective regarding this interaction and the provision of bereavement care. Tweetable abstract: Professionals strive for a serene atmosphere throughout a euthanasia process to ensure relatives can cope with the loss, and the way in which the patient died.